Can quality-attribute requirements be identified from early aspects? : QAMiner: a preliminary approach to quality-attribute mining - Rago, Alejandro (2011)
Specifying good software requirement documents is a difficult task. Many software projects fail because of the omission or bad encapsulation of concerns. A practical way to solve these problems is to use advanced separation of concern techniques, such as aspect-orientation. However, quality attributes are not completely addressed by them. In this work, we present a novel approach to uncover quality-attribute requirements. The identification is performed in an automated-fashion, relying on early asp ects to guide it and using ontologies to model domain knowledge. Our tool was evaluated on two well-known systems, and contrasted with architectural documents.